Public Policy Analysis Of The Implementation Of Constitutional Court Ruling Number 90/PUU-XXI/2023 In The 2024 Election - Maharani Trisni Zulaiha; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
This research is a form of analysis regarding the Constitutional Court Decision Number 90/PUU-XXI/2023 and its implementation as public policy within the framework of the 2024 Election. This analysis is important because Constitutional Court Decision Number 90/PUU-XXI/2023 is seen as a critical decision that is extremely controversial and exceeds the authority of the Constitutional Court itself. This research emphasizes the use of normative legal research, conceptual approaches, and qualitative analysis methods. The results of this research indicate that Constitutional Court Decision Number 90/PUU-XXI/2023 must be constructed separately from the controversy that accompanies it and must be institutionalized constructively. The advice conveyed in this paper is the importance of assuming socialization first regarding the implementation of the new norms settled in Constitutional Court Decision Number 90/PUU-XXI/2023.